Thermoluminescence characteristics of in-house synthesized K₂GdF₅ :Tb powder for photon and neutron - Phan , Van Toan; Nguyen , Van Hung; Pham , Van Dung; Pham , Hung Thai; Le , Ngoc Thiem (Nuclear Science and Technology, 2026)
This work presents an in-house synthesis process of K2GdF5:Tb thermoluminescence (TL) powder by using the solid-state reaction method. The K2GdF5:Tb powder TL glow curves (called as TL spectra), responded to photons (i.e., X-ray beams, gammas) and neutrons, have been investigated to optimize the setting parameters of the TL reader. Batch homogeneity of the in-house synthesized K2GdF5:Tb powder has been investigated to study the feasibility in photon and neutron personal dosimetry. The batch homogeneity of the in-house synthesized K2GdF5:Tb powder was investigated as less than 27.0%, which satisfied the requirement of the IEC and the ISO criteria (maximum of 30.0% is acceptable).